The structural and optical properties of GO: Temperature-dependent analysis of the electrical properties of Al/GO/p-type Si semiconductor structures - Berk, Niyazi; Seymen, Halil; Orak, İkram; Karataş, Şükrü (Elsevier Ltd, 2021)
A spin-coating process has been used to generate graphene oxide (GO) thin films on p-type silicon. The temperature-dependent basic electrical characteristics of Al/GO/p-type Si metal–semiconductor structures have been examined through current–voltage (I–V) measurements in the temperature range 80–420 K by increments of 20 K based on thermionic emission (TE) theory. At each temperature, the main electrical parameters, such as ideality factor (n), rectification ratio (RR), saturation current (I0), barrier height (Φbo), and series resistance (RS), were determined. With increasing temperature, the values of n, I0, RR, and RS decreased, whereas the value of Φbo increased. These unusual temperature fluctuations in Φbo and n may be rationalized in terms of twofold Gaussian distributions at 80–200 K and 220–420 K. For the high- and low-temperature regions, evaluation of these two Gaussian distributions of the I–V curves for the Al/GO/p-type Si structure yielded mean barrier heights of 1.676 and 0.555 eV with standard deviations (σ0) of 166 mV and 76 mV, respectively. Modified ln(I0/T2)−(q2σs2)/(2k2T2) vs. q/(kT) plots, which correspond to these two separate temperature regions, further corroborated these barrier height values. The value of the Richardson constant (A*), 3.567 × 10−6 A K−2 cm−2, is substantially lower than the known value for p-Si. However, for the distribution in the 220–420 K region, the Richardson constant of 48.069 A K−2 cm−2 is near to the known theoretical value of 32 A K−2 cm−2 for p-type Si. © 2021 Elsevier Ltd
Keywords: Barrier inhomogeneity; Optical properties; Structural properties; Al/GO/p-Si structure